Cuci Negeri: Ekofeminis Dalam Sentralitas Ritual Pembersihan Negeri di Soya, Maluku - Pattiasina, Sharon Michelle O. (Institut Agama Kristen Negeri Toraja, 2022)
Abstract: This article aims to explore the ritual of cuci negeri in Soya, Maluku from an ecofeminist perspective. In the current of globalization, humans often make nature as an object so that various forms of oppression occur. However, in Soya's country, nature as a collective home understand nature as a collective home that is cared for through rituals the ritual of cuci negeri. The method used in this research is qualitative with descriptive type. This research uses interview techniques, documentary studies and literature studies. The results of the study found that the washing ritual of the land was a legacy given by the ancestors to make the people of Soya country aware that it came from nature. This awareness is not only affective but also includes the cleaning of the country which is carried out once a year with the aim of maintaining balance with nature and maintaining genealogical relationships with the ancestors. The ritual of cuci negeri also depicts nature as a woman who conceives and gives birth, gives life and protects against all life threats Abstrak: Artikel ini bertujuan untuk menganalisis ritual cuci negeri di Soya, Maluku dalam perspektif ekofeminis. Dalam arus globalisasi, manusia seringkali menjadikan alam sebagai objek sehingga terjadi berbagai bentuk tindakan penindasan. Akan tetapi, dalam realitas masyarakat negeri Soya, mereka memahami alam sebagai rumah secara kolektif yang dirawat melalui ritual cuci negeri. Metode yang digunakan dalam penelitian ini ialah kualitatif dengan jenis deksriptif. Penelitian ini menggunakan teknik wawancara, studi dokumenter dan studi pustaka. Hasil penelitian menemukan bahwa ritual cuci negeri merupakan warisan yang diberikan oleh para leluhur untuk menyadarkan masyarakat negeri Soya yang berasal dari alam. Kesadaran ini tidak hanya sebatas afektif melainkan juga pada tindakan pembersihan negeri yang dilakukan sekali dalam setahun dengan tujuan untuk menjaga keseimbangan dengan alam dan merawat hubungan genealogis bersama para leluhur. Ritual cuci negeri juga menggambarkan alam sebagai sosok perempuan yang mengandung dan melahirkan, memberi kehidupan serta perlindungan terhadap segala ancaman kehidupan.